Comparison of cup placement accuracy using the navigation in total hip arthroplasty between three models using inverse probability of treatment weighting - Shotaro Tachibana; Shinya Hayashi; Yuichi Kuroda; Tomoyuki Kamenaga; Masanori Tsubosaka; Kensuke Wada; Yoshihito Suda; Yuma Onoi; Kemmei Ikuta; Kensuke Anjiki; Naoki Nakano; Tomoyuki Matsumoto; et al. (Journal of Joint Surgery and Research, 2025)
Purpose: This study compared the accuracy of acetabular cup placement between three portable navigation systems during total hip arthroplasty (THA). Furthermore, factors affecting accuracy were investigated. Methods: A total of 101 patients who underwent THA using accelerometer-based navigation, 3D mini-optical navigation, or augmented reality (AR)-based navigation were analyzed. Post-operative cup placement angles were measured using three-dimensional templates. Propensity scores were calculated based on age, sex, body mass index (BMI), and target placement angle. After adjusting for confounding factors using inverse probability of treatment weighting matching, absolute differences in post-operative and intra-operative inclination and anteversion angles were analyzed using one-way analysis of variance (p ​< ​0.05). The backgrounds of outliers (an absolute difference in inclination or anteversion >5°) and non-outliers were compared using t-test and Fisher's exact test. Additionally, logistic regression analysis was performed to calculate the odds ratios of background outliers. Results: The absolute differences in post-operative and intra-operative inclination angles were 2.8°, 3.0°, and 2.9° for accelerometer-based navigation, 3D mini-optical navigation, and AR-based navigation, respectively, with no significant differences. The mean differences in anteversion angles among the groups were 2.2° for accelerometer-based navigation, 2.7° for 3D mini-optical navigation, and 2.2° for AR-based navigation, with no significant differences. BMI was significantly higher in the outlier group (p ​= ​0.03), and logistic regression analysis results showed an odds ratio of 1.2 (p ​= ​0.02). Conclusions: This study demonstrated no significant differences in cup placement accuracy among the three navigation systems after adjusting for confounding factors. High BMI may have affected accuracy.